Bayesian semiparametric additive quantile regression - Elisabeth Waldmann; Thomas Kneib; Yu Ryan Yu; Stefan Lang (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
Quantile regression provides a convenient framework for analyzing the impact of covariates on the complete conditional distribution of a response variable instead of only the mean. While frequentist treatments of quantile regression are typically completely nonparametric, a Bayesian formulation relies on assuming the asymmetric Laplace distribution as auxiliary error distribution that yields posterior modes equivalent to frequentist estimates. In this paper, we utilize a location-scale-mixture of normals representation of the asymmetric Laplace distribution to transfer different flexible modeling concepts from Gaussian mean regression to Bayesian semiparametric quantile regression. In particular, we will consider high-dimensional geoadditive models comprising LASSO regularization priors and mixed models with potentially non-normal random effects distribution modeled via a Dirichlet process mixture. These extensions are illustrated using two large-scale applications on net rents in Munich and longitudinal measurements on obesity among children.
Keywords: 330; asymmetric Laplace distribution; Bayesian quantile regression; Dirichlet process mixtures; LASSO; P-splines